Timing of death and the repeal of the Swedish inheritance tax - Marcus Eliason; Henry Ohlsson (Uppsala University, Department of Economics, 2010)
Does taxation affect the timing of death? This is an interesting example of how behavior might be affected by economic incentives. We study how two changes in Swedish inheritance taxation 2003/04 and 2004/05 have affected mortality during the turns of the years. Our first main result is that deceased with estates taxable for legal heirs were 10 percentage points more likely to have died on New Year' Day 2005, from when the inheritance tax was repealed, rather than on New Year's Eve 2004, compared to deceased without taxable estates for legal heirs. The second main result is that deceased with estates taxable for a married spouse were 12 percentage points more likely to have died on New Year's Day 2004, from when the inheritance tax between spouses was repealed, rather than on New Year's Eve 2003, compared to deceased without taxable estates for a married spouse.
urn:nbn:se:uu:diva-161794
Keywords: H24; H31; I12; 330; behavioral response to taxes; timing of death; estate tax; inheritance tax; tax avoidance; mortality; Sterblichkeit; Erbschaftsteuer; Steuerreform; Steuervermeidung; Verhaltensökonomik; Schweden